The economic cost of public funds in infrastructure investment - Armin Riess (EIB Papers, 2008)
This paper discusses alternative ways of defining and measuring the marginal economic cost of public funds and reviews empirical cost estimates - including estimates for EU countries. Moreover, it illustrates how the economic cost of public funds should be accounted for in cost-benefit analyses of government expenditure, notably on public infrastructure, and how the cost-benefit assessment changes if user fees contribute to the financing of infrastructure services. The paper also clarifies why the economic cost of public funds must not be confused with the social discount rate, social opportunity cost, and the interest rate on government debt. In this context, the paper discusses how government borrowing - that is, taxing later in lieu of taxing now - affects the cost-benefit assessment.
Keywords: 330; Öffentliche Ausgaben; Öffentliche Schulden; Infrastrukturinvestition; Volkswirtschaftliche Finanzierungsrechnung; Theorie; EU-Staaten